2017
DOI: 10.1093/brain/awx015
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring the primary somatosensory cortex in carpal tunnel syndrome with acupuncture

Abstract: Ã These authors contributed equally to this work.Carpal tunnel syndrome is the most common entrapment neuropathy, affecting the median nerve at the wrist. Acupuncture is a minimally-invasive and conservative therapeutic option, and while rooted in a complex practice ritual, acupuncture overlaps significantly with many conventional peripherally-focused neuromodulatory therapies. However, the neurophysiological mechanisms by which acupuncture impacts accepted subjective/psychological and objective/physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 59 publications
2
97
0
16
Order By: Relevance
“…They overestimate their body size and this overestimation is correlated positively with pain and its impact on functionality (Valenzuela-Moguillansky, Reyes-Reyes, & Gaete, 2017). Such perceived body schema distortions can be detected as somatosensory differences and normalized with median nerve stimulation using electroacupuncture (Ho et al, 2014;Maeda et al, 2017). In the context of aforementioned studies and mechanisms, the detected motor loss in SPG in FM may be associated with alleviation of allodynia with MNS through normalization of distorted body schema, which is also detected at SPG during MNS.…”
Section: Correlation Between Mns and Ftt Datamentioning
confidence: 98%
“…They overestimate their body size and this overestimation is correlated positively with pain and its impact on functionality (Valenzuela-Moguillansky, Reyes-Reyes, & Gaete, 2017). Such perceived body schema distortions can be detected as somatosensory differences and normalized with median nerve stimulation using electroacupuncture (Ho et al, 2014;Maeda et al, 2017). In the context of aforementioned studies and mechanisms, the detected motor loss in SPG in FM may be associated with alleviation of allodynia with MNS through normalization of distorted body schema, which is also detected at SPG during MNS.…”
Section: Correlation Between Mns and Ftt Datamentioning
confidence: 98%
“…When subjects with CTS where exposed to electroacupuncture (EA), the severity of their symptoms decreased, and nerve conduction and anatomical separation of cortical digit representations evaluated by fMRI also showed improvements in these subjects. 12 These results showed that, despite the development of aberrant plasticity, these changes can be modulated and somewhat reversed by applying sensory and electrical stimulation in the form of EA.…”
Section: Neural Changes In Maladaptive Plasticitymentioning
confidence: 90%
“…These early studies have been bolstered by more recent human and pre-clinical basic science studies, further defining the mechanistic role of endogenous opioid receptors in acupuncture analgesia (Harris et al, 2009), and suggesting other mechanisms of action including adenosine receptor modulation (Goldman et al, 2010), dopamine signaling for immune regulation (Torres-Rosas et al, 2014), and neuroplasticity in the primary somatosensory cortex of the brain (Maeda et al, 2017). Indeed, clinical trials of acupuncture for chronic pain conditions indicate that acupuncture analgesic effects persist for months following the end of treatment suggesting long term plastic changes in pain processing (MacPherson et al, 2017).…”
Section: Editorial On the Research Topicmentioning
confidence: 99%